An examination of the role of the local government and non government organizations in the management of the Northwest Panay Peninsula low-elevated forest - Bayquin, Sheila M .; Solidum, Fervilynn L. . (2002.)
The study tries to examine the role of the Local Government Units (LGUs) and Non-Government Organizations (NGOs) in the implementation of Philippine forest policy in Northwest Panay Peninsula Low-elevated Forest. The municipal government of Pandan, antique collaborates with the Department of Environment and Natural Resources to introduce community-based forest management. The NGOs on the other hand help in the sourcing of funds for forest conservation projects and of linking local communities with the market. The present study suggests that local government units, NGOs, and other external agents should ahve more clearly defined rules in forest resource management.
Research Paper (Undergraduate, Bachelor of Arts in Economics-Management) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Local government -- Northwest Panay Peninsula